2022
DOI: 10.3390/nano12111851
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the Potential of Fluorinated Ionic Liquids as Interferon-Alpha 2b Delivery Systems

Abstract: Interferon-alpha 2b (IFN-α 2b) is a therapeutic protein used for the treatment of cancer, viral infections, and auto-immune diseases. Its application is hindered by a low bioavailability and instability in the bloodstream, and the search for new strategies for a target delivery and stabilization of IFN-α 2b to improve its therapeutic efficacy is crucial. Fluorinated ionic liquids (FILs) are promising biomaterials that: (i) can form self-assembled structures; (ii) have complete miscibility in water; and (iii) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(39 citation statements)
references
References 73 publications
7
32
0
Order By: Relevance
“…The development of functionalized, bioprivileged, task-specific FILs was previously achieved through the increasing of the perfluoroalkyl sulfonate anion chain ([C F SO ] or greater) [ 37 , 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. These FILs have demonstrated distinct transitions associated with the formation of stable self-assembled structures, which might explain its complete miscibility in water [ 71 ].…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of functionalized, bioprivileged, task-specific FILs was previously achieved through the increasing of the perfluoroalkyl sulfonate anion chain ([C F SO ] or greater) [ 37 , 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. These FILs have demonstrated distinct transitions associated with the formation of stable self-assembled structures, which might explain its complete miscibility in water [ 71 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…The FILs, based on the [C F SO ] anion implemented in this study, demonstrated to be biocompatible and non-toxic in four human cell lines (Caco-2, HepG2, EA.hy926, and HaCaT) and aquatic species with different biological organization levels ( Vibrio fischeri , Daphnia magna , and Lemna minor ) [ 72 , 73 ]. The effects of these biocompatible FILs using lysozyme, BSA, human phenylalanine hydroxylase, and IFN- 2b as model proteins [ 37 , 74 , 75 , 76 , 77 ] were evaluated, proving the [C F SO ]-based FILs as promising potential biomaterials for drug delivery systems using therapeutic proteins. The formation of aqueous biphasic systems using these biocompatible FILs, based on perfluoroalkyl sulfonate anions, was first proposed by one of the authors [ 54 ] as an extractive platform, proving its potential for the efficient and selective extraction of food colorants.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations